Biodegradable metal oxide coated thermoplastic particles
Core-shell particles with a thermoplastic polyester core and partially water-wettable metal oxide shell address dispersibility and biodegradability issues, enabling sustainable use in cosmetic applications by forming stable emulsions and ensuring effective biodegradation.
Patent Information
- Application Number
- JP2024534273
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-16
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2041-12-16
AI Technical Summary
Existing biodegradable and hydrophobic thermoplastic polyester particles are difficult to disperse in aqueous products due to agglomeration, while hydrophilic silica-coated silicon particles lack biodegradability, posing sustainability issues in cosmetic applications.
Development of core-shell particles with a thermoplastic polyester core and a partially water-wettable metal oxide shell, where the shell is permanently attached, allowing for amphiphilic properties and biodegradability, achieved through a method involving emulsification and cooling of a molten polyester with metal oxide particles to form a stable Pickering emulsion.
The core-shell particles exhibit improved dispersibility in both polar and non-polar solvents without additives, maintain amphiphilicity during dispersion, and demonstrate high biodegradability, meeting environmental and cosmetic industry requirements.
Smart Images

Figure 2025500167000001 
Figure 2025500167000002 
Figure 2025500167000003
Abstract
Description
[Technical field]
[0001] The present invention relates to core-shell particles formed from a core of a thermoplastic polyester having a melting range below 160° C. and a shell of partially water-wettable particles of a metal oxide, and to a method for making the core-shell particles. [Background technology]
[0002] Various spherical silica-coated silicon microparticles are known from the prior art, which have good skin feel in cosmetic applications, but are not biodegradable. The use of such particles is not sustainable and is prohibited or limited in many applications by legal regulations.
[0003] Silicon-based core-shell particles, such as those described in WO2021 / 121562 and WA11955S WO2021 / 121561, have a partially hydrophobized surface, and due to their amphiphilic properties they can be easily dispersed in aqueous and organic media.In addition, such particles are virtually non-agglomerating, thereby forming fine and free-flowing powders.However, a drawback of these particles is that they are not biodegradable.
[0004] Prior art biodegradable polyester microparticles, such as those described in EP 3489281 and JP 6543920 B2, are hydrophobic and difficult to disperse in aqueous products, and such uncoated particles have a high tendency to agglomerate weakly and thereby adhere to each other. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2021 / 121562 [Patent Document 2] International Publication No. 2021 / 121561 [Patent Document 3] European Patent Application Publication No. 3489281 [Patent Document 4] Patent No. 6543920 Summary of the Invention
[0006] The present invention relates to a core-shell particle (A), A core (B) comprising a thermoplastic polyester (C) having a melting range of less than 160° C.; and A shell (D) containing partially water-wettable particles (E) of metal oxides having a methanol value of less than 30. wherein the metal content of the core-shell particle (A) is at least 2.5% by weight.
[0007] Surprisingly, the core-shell particles (A) of the present invention are readily biodegradable ("easily biodegradable"), which can be measured by the CO2 evolution test (Sturm test) according to OECD 301B. This is very surprising and unexpected, since it is known to those skilled in the art that the partially water-wettable particles (E) that form a shell (D) permanently attached around the core (B) of biodegradable thermoplastic polyester are themselves difficult to dissolve and are not biodegradable. Thereby, the core-shell particles (A) of the present invention meet the demand of the cosmetics industry for environmentally friendly biodegradable microparticles.
[0008] The permanently attached shell (D) of the partially water-wettable particles (E) is a significant advantage over finely divided particles in the solid state, such as prior art thermoplastic polyester particles that are treated with silica as an antiblocking agent or as a flow improver, in which the silica is not permanently attached to the surface.
[0009] The core-shell particles (A) of the present invention are amphiphilic, i.e. they are both hydrophilic (i.e. water-loving) and lipophilic (i.e. fat-loving). This means that the core-shell particles (A) of the present invention are easily dispersible in both polar solvents, such as water or alcohol, and non-polar solvents, such as aliphatic hydrocarbons, or polydimethylsiloxane oils, without the addition of further dispersing aids or additives, such as organic emulsifiers or other surface-active substances. This is a significant advantage of the particles (A) compared to uncoated prior art particles, which are very hydrophobic and cannot be dispersed in polar solvents, such as water or alcohol, without the use of undesirable aids, such as organic emulsifiers. In the core-shell particles (A) of the present invention, the particles (E) are firmly attached to the surface, so that the amphiphilicity is maintained when dispersed in a solvent. This is a significant advantage over prior art thermoplastic polyester particles that undergo post-treatment with silica after curing, because the silica is not permanently attached in these non-invention particles.
[0010] The core-shell particles (A) of the present invention have a structured surface, which results in improved oil absorption compared to conventional uncoated thermoplastic polyester particles of the prior art, such as those described in US11078338BB and JP6794499B2.
[0011] The present invention also relates to a method for producing a core-shell particle (A), the core-shell particle (A) comprising: A core (B) comprising a thermoplastic polyester (C) having a melting range of less than 160° C.; and A shell (D) containing partially water-wettable particles (E) of metal oxides having a methanol value of less than 30. wherein the metal content of the core-shell particles (A) is at least 2.5% by weight; In a first step, a thermoplastic polyester (C) is heated above its melting range, thereby becoming free-flowing, and emulsified with particles (E) in water to form a particle-stabilized oil-in-water emulsion (G) having a discontinuous phase comprising molten polyester (C) and a water-containing continuous phase; In a second step, the emulsion (G) is cooled below the melting range of the polyester (C) such that the molten particle-stabilized polyester droplets (C) solidify and the particles (E) adhere to the surfaces of the polyester particles (C) to form core-shell particles (A).
[0012] A process in which the solidified thermoplastic melt (C) forms the core (B) of a core-shell particle (A) and a particulate emulsifier (E) forms the shell (D).
[0013] In principle, any thermoplastic polyester (C) or a blend of different thermoplastic polyesters (C) can be used. The melting temperature is preferably in the range of 45 to 160°C, preferably in the range of 50 to 155°C, more preferably in the range of 85 to 150°C.
[0014] If the melting temperature is below 45°C, the resulting particles (A) are no longer suitable for many applications, such as products manufactured at high temperatures, such as lipstick, which complicates storage, since the storage temperature must be monitored.If the melting temperature is higher than 160°C, processing according to the method of the present invention is only possible with very high technical complexity and high costs.Thermoplastic polyester (C) may also discolor or decompose during processing at temperatures higher than 160°C.
[0015] Examples of suitable thermoplastic polyesters (C) include polycaprolactone (PCL), poly(butylene succinate) (PBS), poly(butylene succinate adipate) (PBSA), poly(butylene adipate terephthalate) (PBAT), polyhydroxyalkanoates (PHAs), polyhydroxybutyrates (PHBs), polyhydroxyvalerates (PHVs), poly(hydroxybutyrate hydroxyvalerate) copolymers (PHBVs), or blends thereof, with unblended polyesters being preferred.
[0016] Polycaprolactone (PCL), poly(butylene succinate) (PBS), poly(butylene succinate adipate) (PBSA), poly(butylene adipate terephthalate) (PBAT) and poly(hydroxybutyrate-co-hydroxyvalerate) or blends thereof are preferred, with unblended polyesters being preferred. Particularly preferred are poly(butylene succinate) (PBS), poly(butylene succinate adipate) (PBSA) and poly(butylene adipate terephthalate) (PBAT).
[0017] The term "biodegradable" as used herein should be understood to include all polyesters that are degraded by the action of living organisms, light, air, water, or a combination thereof. Biodegradation reactions are usually catalyzed by enzymes and usually occur in the presence of moisture. The hydrophilicity / hydrophobicity of a polymer has a large effect on its biodegradability, with polar polymers usually being more readily biodegradable. Other important polymer properties that affect biodegradability are the degree of crystallinity, chain flexibility, and chain length.
[0018] Preferably, the thermoplastic polyester C is particularly readily biodegradable ("readily biodegradable"), which can be measured by the CO2 evolution test (Sturm test) according to OECD 301B. This method is based on the production of CO2. The biodegradability is measured at the end of what is called a 10-day test window and after 28 days of testing. If a product has achieved the required degradation level of at least 60% both at the end of the 10-day window and after 28 days of incubation, it is described as readily biodegradable.
[0019] The core-shell particles (A) of the present invention achieve a biodegradability according to OECD 301B of at least 60%, preferably at least 65%, more preferably at least 70%.
[0020] The processability of the thermoplastic polyesters (C) can be improved by adding suitable additives, such as plasticizers, flow improvers or lubricants. Methods for this are known to the person skilled in the art.
[0021] Further prior art additives can be added to the thermoplastic polyester (C) to improve the thermoplastic properties. Examples include light stabilizers, antioxidants, fillers, dyes and pigments, plasticizers, and antistatic agents. Other additives can improve processability. Examples include lubricants, heat stabilizers, and foaming agents.
[0022] Preferably, no further auxiliaries or additives are added.
[0023] Commercially available thermoplastic polyesters often have very high melt viscosities, exceeding 500,000 mPa·s. Although such polymer melts can be processed by the method of the present invention, their processing and emulsification entails relatively high technical complexity and generally only results in relatively large and / or irregularly shaped particles. Such products are useful, for example, in cleansing creams, washing gels or exfoliating scrubs.
[0024] Preferred small and essentially spherical microparticles are produced from thermoplastic polyesters (C) which have a melt viscosity at the temperature during emulsification of less than 500000 mPa·s, preferably less than 250000 mPa·s, more preferably less than 150000 mPa·s and in particular less than 100000 mPa·s.
[0025] In the process of the present invention, the partially water-wettable particles (E) act as particulate emulsifiers and stabilize oil-in-water emulsions of the thermoplastic melt, such emulsions being known as Pickering emulsions.
[0026] The particles (E) are metal oxides having a covalent component in the metal-oxygen bond, for example solid oxides of main and transition group elements, for example one of main group 3, such as boron oxide, aluminum oxide, gallium oxide or indium oxide, or one of main group 4, such as silicon dioxide, germanium dioxide, tin oxide or tin dioxide, or lead oxide or lead dioxide, or oxides of transition group elements, such as titanium dioxide, zirconium dioxide, hafnium dioxide, cerium oxide or iron oxide.
[0027] At room temperature and the pressure of the ambient atmosphere, i.e. 1013 hPa, the particle (E) exists as a solid particle.
[0028] Preferably, the particles (E) are metal oxides having a covalent component in the metal-oxygen bond, such as solid oxides of main group and transition group elements, such as one of main group 3, such as boron oxide, aluminum oxide, gallium oxide or indium oxide, or one of main group 4, such as silicon dioxide, germanium dioxide, tin oxide or tin dioxide, or lead oxide or lead dioxide, or oxides of transition group elements, such as titanium dioxide, zirconium dioxide, hafnium dioxide, cerium oxide or iron oxide.
[0029] Preferably, the particles (E) are aluminum oxide (III), titanium oxide (IV) or silicon oxide (IV), for example wet-chemically produced, for example precipitated silica or silica gel, or aluminum oxide, titanium dioxide or silicon dioxide produced in a high-temperature process, for example pyrogenic aluminum oxide, titanium dioxide or silica, with fumed silica being particularly preferred.
[0030] At pH 7.33, 0.11 molar electrolyte background and a temperature of 37° C., the particles (E) preferably have a solubility in water at the pressure of the ambient atmosphere, ie 1013 hPa, of less than 0.1 g / l, more preferably less than 0.05 g / l.
[0031] Preferably, the particles (E) have a molar mass of more than 10 000 g / mol, more preferably from 50 000 to 50 000 000 g / mol, in particular from 100 000 to 10 000 000 g / mol, in each case preferably measured by static light scattering.
[0032] Preferably, the particles (E) have a diameter of 30 to 500 m 2 / g, more preferably 100 to 300m 2 The BET specific surface area is determined according to known methods, preferably in accordance with German Industrial Standards DIN 66131 and DIN 66132.
[0033] Preferably, the particles (E) have a Mohs hardness of greater than 1, more preferably greater than 4.
[0034] Particles (E) are characterized in that they are surface-treated with a suitable hydrophobizing agent, resulting in hydrophobicity. Hydrophobization must be performed so that particles (E) are still partially water-wettable. According to the present invention, this means that the methanol value of particles (E) is less than 30, preferably less than 25, more preferably less than 20.
[0035] As a result of the surface treatment, the preferred particles (E) have a carbon content of at least 0.2% by weight and up to 1.5% by weight, preferably between 0.4% by weight and 1.4% by weight, more preferably between 0.6% by weight and 1.3% by weight. The hydrophobic groups are, for example, Si-bonded methyl or vinyl groups. Methods for the hydrophobization of silica are known to those skilled in the art.
[0036] Very particular preference is given to the partially water-wettable silicas described in EP 1 433 749 A1 and DE 10 349 082 A1.
[0037] Particularly preferred particles (E) are silanized fumed silica having a methanol value of less than 30.
[0038] In this case, the average particle size of the particles (E) or particle agglomerates, if present, is preferably smaller than 50x the median diameter of the droplets free of fine particles.
[0039] The average particle size of the particles (E) is preferably less than 1000 nm, more preferably between 10 nm and 800 nm, particularly preferably between 50 nm and 500 nm, most preferably between 75 nm and 300 nm, in each case measured as the average hydrodynamic equivalent diameter by photon correlation spectroscopy at 173° (backscattering) using a Nanosizer ZS from Malvern.
[0040] To measure the methanol value, defined mixtures of water and methanol are prepared and the surface tension of these mixtures is then measured using known methods. In separate experiments, these water-methanol mixtures are overlaid with a defined amount of particles and shaken under defined conditions (e.g., gentle manual shaking or shaking with a tumble mixer for about 1 minute). Water-alcohol mixtures in which the particles have not yet sunk and water-alcohol mixtures with higher alcohol content in which the particles have just sunk are measured. The surface tension of the latter alcohol-water mixture gives the critical surface energy γcrit as a measure of the surface energy γ of the particles. Its methanol content in water gives the methanol value.
[0041] The core-shell particles (A) of the present invention preferably have a size x 50 of 1 to 100 μm, preferably 2 to 50 μm, more preferably in particular 2 to 20 μm, in particular 3 to 10 μm.
[0042] The core-shell particles (A) of the present invention are preferably essentially spherical. Preferably, the sphericity SPHT3 is at least 0.80, preferably at least 0.82, in particular at least 0.85, which can be measured according to ISO 9276-6 using a Camsizer X2 from Retsch Technology.
[0043] The particles (A) of the present invention have a core-shell structure, with the thermoplastic polyester (C) forming the core and the particulate emulsifier (E) forming the shell.
[0044] The core of the core-shell particles (A) of the present invention is essentially filled and does not contain pores. They differ in this respect from the porous particles described, for example, in JP6543920B2. It has also been found that the particles produced according to EP3489281A1 have a porous structure. The disadvantage of this type of porous particles is that, as a result of trapped air bubbles, they tend to float when incorporated into liquid products.
[0045] The particles (A) are particularly characterized in that the particles (E) used essentially adhere to the surface of the polymer particles (A), thereby forming a shell (D) around the core (B) of thermoplastic polyester (C). The distribution of the particles (E) used can be obtained from TEM images of thin sections of the embedded particles of the invention. The average diameter of the shell (D) of the particles (E) is preferably greater than 10 nm, more preferably greater than 20 nm, particularly preferably greater than 30 nm.
[0046] The core-shell particles (A) according to the invention are characterized in that the shell (D) is permanently attached, in this context "permanently attached" means that the average diameter (D) of the shell is preferably greater than 10 nm, more preferably greater than 20 nm, particularly preferably greater than 30 nm, even after the particles have been washed three times with water.
[0047] Preferred core-shell particles (A) have a shell (B) of partially water-wettable silica, the silicon content of which is in each case at least 1% by weight, preferably at least 2% by weight, more preferably at least 3% by weight and particularly preferably at least 4% by weight, based on the core-shell particle (A).
[0048] The linseed oil absorption of the core-shell particles (A) of the present invention, measured according to the method described in EP3489281A1, is preferably in the range of 150 ml to 300 ml per 100 g of particles (A), more preferably in the range of 160 ml to 250 ml per 100 g of particles (A), and particularly preferably in the range of 200 ml to 250 ml per 100 g of particles (A).
[0049] The linseed oil absorption of the particles (A) is measured using a method modified from that of JIS K5101-13-2-2004, in which refined linseed oil is used instead of boiled linseed oil, and the end point is the point at which the paste of the particles (A) mixed and kneaded with refined linseed oil begins to flow when the measurement plate is in an upright position. The detailed measurement of the linseed oil absorption is as follows:
[0050] (A) Equipment and tools Measurement plate: Smooth glass plate larger than 300 x 400 x 5 mm Palette knife (spatula): made from steel or stainless steel, with a blade and a handle Analytical balance: Allows measurements up to 10 mg Burette: Capacity is 10ml according to JIS R3505:1994
[0051] (B) Reagents Refined linseed oil: according to ISO 150:1980 (in this example, first grade linseed oil (produced by Wako Pure Chemical Industries) is used).
[0052] (C) Measurement method (1) Place 1 g of particles (A) in the center of the measurement plate, gradually add 4 to 5 drops of refined linseed oil to the center of the particles (A) using a burette, and after each drop, thoroughly mix the particles (A) and refined linseed oil with a palette knife.
[0053] (2) After repeated dropping and kneading, when the particles (A) and refined linseed oil have become a putty-like solid mass, the refined linseed oil is dropped into the mixture. The end point is the point at which the paste (particles (A) mixed and kneaded with refined linseed oil) suddenly becomes soft and starts to flow after the refined linseed oil has been dropped into the mixture.
[0054] (3) Judgment of flow The paste is considered to be flowing if it suddenly softens and moves when the measuring plate is in the upright position after the addition of the drop of refined linseed oil. If the paste does not move when the measuring plate is in the upright position, add another drop of refined linseed oil.
[0055] (4) At the end point, read the amount of refined linseed oil consumed, which is the amount of liquid that falls into the burette.
[0056] (5) Measurements shall be completed within 7 to 15 minutes. If a measurement takes longer than 15 minutes, another measurement shall be taken and the result shall be the value obtained from the measurement completed within the specified time.
[0057] (D) Calculation of Linseed Oil Absorption The linseed oil absorption per 100 g of sample is calculated according to the following formula: O = (V / m) x 100 In the formula, O: linseed oil absorption amount (ml / 100g), m: weight of particle (A) (g), V: volume of refined linseed oil consumed (ml)
[0058] The process for preparing the core-shell particles (A) does not require the use of organic auxiliaries, emulsifiers or solvents.
[0059] Preferably, a three-phase mixture is formed in which a poorly water-soluble and water-immiscible, melting, and thereby free-flowing, emulsion (G) of thermoplastic polyester (C) is produced, stabilized by partially water-wettable particles (E) in the aqueous phase (Pickering emulsion).
[0060] Surprisingly, by the process of the invention it is possible to produce Pickering emulsions (G) of molten thermoplastic polyesters at high temperatures, thereby avoiding the disadvantageous use of organic solvents.
[0061] Thus, in a preferred embodiment, the polyester (C) heated above its melting range is emulsified to the exclusion of organic solvents.
[0062] The particle-stabilized oil-in-water emulsion (G) has a continuous aqueous phase, which is not altered in the second step.
[0063] Preferably, the continuous phase contains at least 80% by weight, especially at least 90% by weight, of water.
[0064] The size of the particles (A) can be determined, for example, by emulsification techniques, whereby variables such as, for example, the input shear energy, the volume fraction of the thermoplastic polyester (C), the amount of partially water-wettable particles (E), the pH of the continuous aqueous phase and its ionic strength, the viscosity, the dosing sequence, the dosing rate, or by the process regime, i.e., for example, the temperature, the mixing time, and the concentrations of the raw materials used.
[0065] When using emulsification techniques that allow the generation of relatively small droplets, the process gives small surface-structured particles (A). For this purpose, it is possible, for example, to stabilize the melted and thus free-flowing thermoplastic polyester (C) in water using different shear energies or the selection of different partially water-wettable particles (E).
[0066] The emulsion (G) may optionally contain an organic emulsifier.
[0067] By organic emulsifiers is meant here not particles and colloids but rather molecules and polymers which comply with the definition of molecules, polymers, colloids and particles given in Dispersionen and Emulsionen, G. Lagaly, O. Schulz, R. Zindel, Steinkopff, Darmstadt 1997, ISBN 3-7985-1087-3, pp. 1 to 4.
[0068] Generally, these organic emulsifiers have a size less than 1 nm, a molar mass less than 10 000 g / mol, a carbon content greater than 50% by weight (measurable by elemental analysis) and a Mohs hardness less than 1.
[0069] At the same time, the organic emulsifiers essentially absent in the emulsions of the invention generally have a solubility in water, in homogeneous or micellar form, of more than 1% by weight at 20° C. and the pressure of the ambient atmosphere, ie 1013 hPa.
[0070] Emulsion (G) may contain such organic emulsifiers up to a maximum concentration of less than 0.1 times, preferably less than 0.01 times, more preferably less than 0.001 times and in particular less than 0.0001 times the critical micelle concentration of these organic emulsifiers in the aqueous phase, which corresponds to a concentration of these organic emulsifiers of less than 10% by weight, preferably less than 2% by weight, more preferably less than 1% by weight and in particular 0% by weight, based on the total weight of the dispersion of the invention.
[0071] Preferably, the particle-stabilized Pickering emulsion (G) is essentially free of conventional organic surface-active substances that are non-particulate liquids and solids at room temperature and ambient pressure, such as nonionic, cationic, and anionic emulsifiers ("organic emulsifiers").
[0072] First process step
[0073] The thermoplastic polyester (C) is heated above its melting range, melts, becomes free-flowing, and is emulsified in water with the partially water-wettable particles (E) to form a particle-stabilized oil-in-water emulsion (Pickering emulsion).
[0074] Preferably, a dispersion (H) of the partially water-wettable particles (E) in water is formed prior to mixing with the melted and thereby free-flowing thermoplastic polyester (C).
[0075] Dispersion (H) can in principle be prepared according to known methods for preparing particle dispersions, such as incorporation using stirrers with high shear effects, such as high-speed stirrers, high-speed dissolvers, rotor-stator systems, ultrasonic dispersers or ball / bead mills.
[0076] Here, the concentration of the partially water-wettable particles (E) in the dispersion (H) is between 1% and 80% by weight, preferably between 10% and 60% by weight, more preferably between 10% and 40% by weight, most preferably between 12% and 30% by weight.
[0077] For the preparation of the particle-stabilized Pickering emulsion (G) in the first step, any method for preparing an emulsion known to the skilled artisan can be used. However, it has been found that an emulsion that is particularly suitable for preparing particles (A) can be obtained according to the following process.
[0078] Process 1: - The highly concentrated dispersion (H) is charged first, the volume initially charged being such that it contains only a part of the total amount of particles (E) required and the volume of water. The total volume of polyester (C) is metered in slowly under constant homogenization, for example by means of a high-speed stirrer, a high-speed dissolver or a rotor-stator system. - The remainder of the desired volume of water is then metered in slowly, optionally under constant homogenization, for example by means of a high-speed stirrer, a high-speed dissolver or a rotor-stator system.
[0079] Process 2: - The dispersion (H) of particles (E) is charged first, the volume charged first being such as to contain the total amount of particles (E) and water required. The total volume of polyester (C) is metered in slowly under constant homogenization, for example by means of a high-speed stirrer, a high-speed dissolver, a rotor-stator system or a capillary emulsifier.
[0080] Process 3: - The total volume of polyester (C) is charged first. - A concentrated dispersion (H) of particles (E) in water is slowly metered in under constant homogenization, for example with a high-speed stirrer, high-speed dissolver or rotor-stator system, the initially charged volume being such that it contains the total amount of particles (E) required and only a part of the water volume. - The remainder of the desired volume of water is then metered in slowly, optionally under constant homogenization, for example by means of a high-speed stirrer, a high-speed dissolver or a rotor-stator system.
[0081] Step 4: - The total volume of polyester (C) is charged first. - A dispersion (H) of particles (E) in water is slowly metered in under constant homogenization, for example using a high-speed stirrer, a high-speed dissolver or a rotor-stator system, the volume initially charged being such that it contains the total amount of particles (E) and water required.
[0082] Process 5: The total volume of polyester (C) and the dispersion (H) of particles (E) in water are initially charged, the volume initially charged being such as to contain the total amount of particles (E) and water required. - Homogenization of both together is carried out, for example, by means of a high speed stirrer, a high speed dissolver or a rotor-stator system.
[0083] Process 6: The total volume of polyester (C) and the concentrated dispersion (H) of particles (E) in water are initially charged, the volume initially charged being such as to contain the total amount of particles (E) required and part of the volume of water. - Homogenization of both together is carried out, for example, by means of a high speed stirrer, a high speed dissolver or a rotor-stator system. - The remainder of the desired volume of water is then metered in slowly, optionally under constant homogenization, for example by means of a high-speed stirrer, a high-speed dissolver or a rotor-stator system.
[0084] Processes 1, 2, 5 and 6 are preferred, processes 2 and 5 are more preferred, and process 5 is especially preferred.
[0085] Homogenization is preferably carried out for at least 30 seconds, preferably at least 1 minute, in at least one process step.
[0086] The dispersion (H) of particles (E) in water, which forms a homogeneous phase in the emulsion (G), can in principle be prepared according to known processes for producing particle dispersions, for example by incorporation using stirrers with high shear effects, such as high-speed stirrers, high-speed dissolvers, rotor-stator systems, ultrasonic dispersers or ball / bead mills.
[0087] The process described can be carried out either continuously or discontinuously, with continuous operation being preferred.
[0088] The temperature in the first step is above the melting temperature of the thermoplastic polyester (C), above which the thermoplastic polyester (C) is in a free-flowing state, preferably within a temperature range of 45 to 180° C., preferably 50 to 170° C., more preferably 85 to 165° C. Preferably, the temperature in the first step is at least 5° C., preferably at least 10° C., higher than the melting temperature of the thermoplastic polyester (C). Higher processing temperatures can result in discoloration and degradation of the thermoplastic polyester, significantly increasing the technical complexity of the processing.
[0089] The emulsification process in the first step can be carried out at standard pressure, i.e. 900-1100 hPa, at elevated pressure, or under reduced pressure. If the process temperature is below 100° C., a process at standard pressure is preferred. If the process temperature is above 100° C., a process at elevated pressure is preferred, and the selected pressure is preferably high enough that the boiling temperature exceeds the process temperature. The dependence of the physical state of water on pressure and temperature is known to those skilled in the art. For example, water is in the liquid state at a temperature of 160° C. and a pressure of 10 bar. Preferably, the pressure in the emulsification process is less than 50 bar, more preferably less than 20 bar, particularly preferably less than 10 bar.
[0090] The concentration of the partially water-wettable particles (E) in the three-phase mixture (G) of the dispersion (H) from the first step and the thermoplastic polyester (C) is between 1% and 20% by weight, preferably between 2% and 15% by weight, more preferably between 3% and 12% by weight.
[0091] The concentration of the molten and thus free-flowing thermoplastic polyester (C) in the three-phase mixture (G) of the dispersion (H) from the first step and the thermoplastic polyester (C) is between 50% and 80% by weight, preferably between 53% and 70% by weight, more preferably between 55% and 68% by weight.
[0092] The concentration of water in the three-phase mixture (G) of the dispersion (H) from the first step and the thermoplastic polyester (C) is between 10% and 48% by weight, preferably between 15% and 45% by weight, more preferably between 23% and 40% by weight, most preferably between 25% and 36% by weight.
[0093] In an optional process step, the Pickering emulsion (G) is diluted with water, optionally under constant homogenization, for example using a high speed stirrer, a high speed dissolver or a rotor-stator system.
[0094] Optional upstream process steps (melt viscosity reduction): The melt viscosity of the thermoplastic polyester (C) can be reduced in an optional process step prior to producing the three-phase mixture (G), thereby improving its emulsification properties. Suitable processes are known to those skilled in the art.
[0095] Preferably, the melt viscosity is reduced by transesterification, for example by reacting a thermoplastic polyester having a relatively high melt viscosity with a thermoplastic polyester having a relatively low melt viscosity, thereby reducing the melt viscosity, said polyesters being able to be chemically identical or chemically different.
[0096] Similarly, the thermoplastic polyester having a high melt viscosity can be reacted with a suitable end stopper (I), preferably a monofunctional alcohol or a monofunctional carboxylic acid, in a transesterification reaction, thereby reducing the melt viscosity. Here, the monofunctional alcohol or monofunctional carboxylic acid acts as an end group. Any desired combination of the thermoplastic polyester (C) having a relatively low melt viscosity with the monofunctional alcohol and monofunctional carboxylic acid can also be used. Monofunctional alcohols are preferred.
[0097] The melt viscosity of the thermoplastic polyester (C) can be adjusted by the type and amount of the thermoplastic polyester and alcohol or carboxylic acid with a relatively low melt viscosity, and the more used, the lower the melt viscosity obtained. This is known to those skilled in the art. Those skilled in the art also know that the type and amount of the thermoplastic polyester or alcohol or carboxylic acid with a relatively low melt viscosity selected for reaction also affects the chemical, physical, and mechanical properties of the thermoplastic polyester obtained. For example, hardness, toughness, elasticity, or polarity can be increased or decreased.
[0098] Preferably, the boiling point of the monofunctional alcohol or monofunctional carboxylic acid is higher than the melting temperature of the thermoplastic polyester (C).
[0099] In principle, any monofunctional alcohol is suitable. For example, they can be primary, secondary or tertiary alcohols with aliphatic or aromatic groups, preferably primary or secondary alcohols, more preferably primary alcohols. The alcohol can be branched or linear, can have aromatic or functional groups, and can be saturated or unsaturated. It can also be a polyether that is hydroxy-functional at one end. Mixtures of monofunctional alcohols can also be used.
[0100] Preferred alcohols are monofunctional saturated or unsaturated alcohols having aliphatic or aromatic groups, preferably C4 to C30, preferably C6 to C26. Particularly preferred are primary aliphatic C6 to C12 alcohols and mixtures thereof, and primary aliphatic C16 to C24 alcohols and mixtures thereof.
[0101] In principle, any monofunctional carboxylic acid is suitable. For example, they can be carboxylic acids with aliphatic or aromatic groups. The carboxylic acid can be branched or linear, aromatic or functional, saturated or unsaturated. It can also be a polyester with carboxy functionality at one end. Mixtures of monofunctional carboxylic acids can also be used.
[0102] Preferred carboxylic acids are monofunctional saturated or unsaturated carboxylic acids having an aliphatic or aromatic group, preferably C4 to C30, preferably C6 to C26. Particularly preferred are monofunctional aliphatic C6 to C12 carboxylic acids and mixtures thereof, and monofunctional aliphatic C16 to C24 carboxylic acids and mixtures thereof.
[0103] The transesterification reaction is preferably accelerated by suitable catalysts, which are known to those skilled in the art. Suitable catalysts are, for example, inorganic or organic acids or bases, metal salts and metal complexes, for example of lithium, aluminum, titanium, zirconium, tin or lead.
[0104] Examples of such catalysts are, in particular, tin or zinc carboxylates in which a hydrocarbon group is directly bonded to the tin, such as di-n-butyltin dilaurate, tin octoate, di-2-ethyltin dilaurate, di-n-butyltin di-2-ethylhexoate or di-2-ethylhexyltin di-2-ethylhexoate, dibutyl- or dioctyltin diacylate, in which the acylate groups are in each case derived from alkanoic acids having 3 to 16 carbon atoms per acid, at least two of the valences of the carbon atoms bonded to the carboxyl groups being occupied by at least two carbon atoms other than the valences of the carboxyl groups, and zinc octoate. Other examples of catalysts (3) are alkoxy titanates, such as butoxy titanate and triethanolamine titanate, and also zirconium and aluminum compounds, in particular the carboxylates and alkoxides thereof.
[0105] Preferably, the condensation catalyst is used in an amount of 0.1% by weight to 10% by weight based on the total of the polyester (C) and the alcohol or carboxylic acid.
[0106] The transesterification reaction is preferably carried out for 30 minutes to 48 hours in the temperature range between 40 and 200° C., preferably for 60 minutes to 24 hours in the temperature range between 60 and 180° C. Longer reaction times reduce polydispersity and improve quality.
[0107] In the transesterification reaction, the thermoplastic polyester (C) can be dissolved in a suitable solvent. Preferably, the transesterification reaction is carried out without the addition of a solvent.
[0108] In a preferred embodiment, the transesterification reaction is carried out without the addition of a solvent at a temperature above the melting range of the thermoplastic polyester (C).
[0109] Examples of suitable mixers are laboratory stirrers, kneaders, planetary mixers or dissolvers, rotor-stator systems, or extruders.
[0110] In a preferred embodiment, an optional upstream process step (melt viscosity reduction) is performed.
[0111] Starting from the above mentioned three-phase mixture (G), the particles (A) are obtained in a second process step by cooling the Pickering emulsion (G) below the melting temperature of the thermoplastic polyester (C).
[0112] Preferably, the three-phase mixture (G) is cooled in a second process step to a temperature 10° C. below the melting temperature of the thermoplastic polyester (C), preferably 20° C. below the melting temperature, more preferably 30° C. below the melting temperature. In a particularly preferred embodiment, the temperature of the three-phase mixture (G) is cooled to less than 40° C., preferably less than 30° C., before the particles (A) are further isolated or processed.
[0113] In the second step, the process must be carried out in such a way that, during cooling, the partially water-wettable particles (E) stabilizing the discontinuous phase enter into stable interactions, such as hydrogen bonds, van der Waals interactions, or any other directional interactions, or a combination of such directional interactions, with the surface of the thermoplastic polyester (C) forming the core, so that the partially water-wettable particles (E) are permanently fixed to the core formed from the thermoplastic polyester (C).
[0114] The duration of the second process step is preferably less than 24 hours, preferably between 0 hours and 18 hours, more preferably between 0.1 hours and 6 hours, and in a specific implementation between 0.15 hours and 2 hours.
[0115] Optionally, water can be added to the three-phase mixture (G), thereby cooling the mixture.
[0116] Optionally, dispersing aids, protective colloids and / or surfactants may be added to the three-phase mixture (G). These may be added in the first step or before or during the second step.
[0117] Preferably, the three-phase mixture (G) contains less than 5% by weight, more preferably less than 1% by weight, in particular less than 0.1% by weight of dispersing agents, protective colloids, and surfactants. In a specific implementation, the three-phase mixture does not contain dispersing agents, protective colloids, and surfactants.
[0118] Optionally, the three-phase mixture (G) contains an inorganic or organic electrolyte, which can be added either after the first step, during the second step, or after completion of the second step.
[0119] In this case, the ionic strength of the three-phase mixture is between 0.01 mmol / l and 1 mol / l, preferably between 0.1 mmol / l and 500 mmol / l, more preferably between 0.5 mmol / l and 100 mmol / l.
[0120] Optionally, the surface of the particles (A) may be modified by treatment with reactive silanes or siloxanes. These may be added immediately after the completion of the production of the Pickering emulsion (G) in a first step, during the reaction stage, after the completion of the reaction stage in a second step, before the isolation of the particles (A) or after the isolation of the particles in the liquid or solid phase. The treatment must be carried out so that a covalent chemical bond of the silane or siloxane to the particles (A) occurs. Suitable methods and processes are known to the person skilled in the art.
[0121] The solid content of the particles (A) in the three-phase mixture (G) consists of the sum of the thermoplastic polyester (C) and the partially water-wettable particles (E). Preferably, the solid content of the three-phase mixture in the second process step ranges between 5% and 70% by weight, preferably between 20% and 60% by weight, more preferably between 35% and 50% by weight.
[0122] If the solid content is high, the particles (A) may stick to each other.
[0123] Optionally, the three-phase mixture (G) after the second step may be stored under continued stirring, which can be done, for example, using a paddle stirrer or an anchor stirrer.
[0124] In a preferred embodiment, the particles (A) are preferably isolated by sedimentation, filtration or centrifugation, more preferably by filtration or centrifugation, particularly preferably by centrifugation.
[0125] After isolation, the particles (A) are preferably washed with a washing liquid, preferably selected from demineralized water, methanol, ethanol, and mixtures thereof.
[0126] In a preferred embodiment, the particles (A) are isolated from the aqueous phase in powder form, for example by filtration, sedimentation, centrifugation, or by drying in an oven or oven, or by spray drying, or by applying a suitable reduced pressure to remove volatile materials.
[0127] If the particles (A) are mixed during drying, as in the case of spray drying, cone drying, paddle drying or fluidized bed drying, very high particle fineness (A) can be achieved without further processing. Statically dried particles (A) tend to form loose agglomerates that can be deagglomerated by gentle processes such as sieving or mixing. Optionally, the particles (A) can also be deagglomerated by a suitable comminuting process such as ball milling or air jet milling.
[0128] The particles (A) can be used, inter alia, as a component of cosmetics such as foundations, antiperspirants, and peeling scrubs, an auxiliary for paints, a leveling agent or rheology modifier for paints, a rheology regulator, an antiblocking agent, a lubricant, a light scattering agent, an auxiliary for fine ceramics such as a component for sintering molding or fine ceramics, a filler for adhesives, a medical diagnostic agent, and an additive for molded products such as automotive materials and building materials.
[0129] <Measurement method>
[0130] - Median particle size (x50): Particle size (median diameter x 50) and sphericity SPHT analysis was performed using a Camsizer X2 from Retsch Technology (measurement principle: dynamic image analysis) according to ISO 13322-2 and ISO 9276-6 (analysis type: dry measurement of powders and granules; measurement range: 0.8 μm to 30 mm; compressed air dispersion with "X-Jet"; dispersion pressure = 0.3 bar). c min The evaluation was carried out on a volumetric basis according to the model.
[0131] - Melting Point Measurement by differential scanning calorimetry (DSC) according to DIN EN ISO 11357-3 with a Netzsch DSC 214 Polymer analyzer: sample weight: 8.5 mg, temperature range -70 to 150 °C, heating / cooling rate 10 K / min; the measurement included two runs (each run consisting of the following heating and cooling cycles: -70 °C (10 K / min) to 150 °C and 150 °C (10 K / min) to -70 °C); the second run was used for the evaluation.
[0132] - Molecular weight measurement The weight average molecular weight Mw and number average molecular weight Mn were determined by size exclusion chromatography (SEC) against polystyrene standards in THF on a Styragel HR1-HR3-HR4-HR5 column set from Waters USA, with an injection volume of 10 μl and a sample concentration of 10 mg / ml, at 60° C. and a flow rate of 0.4 ml / min, with detection by RI (refractive index detector).
[0133] - Melt Viscosity The melt viscosity was measured on an Anton Paar MCR 302 rheometer according to DIN EN ISO 3219-1 / 2 and DIN 53019 with parallel plates / plates using a temperature gradient at decreasing deformation and constant frequency.
[0134] The measurement parameters were selected as follows: - Measurement system PP25 (calculation mode: conversion constant at maximum radius) - Measurement points were recorded every 30 seconds Section 1 - Temperature gradient: 180℃~-50℃(2K / min) - Deformation gradient: 0.2%~0.1% logarithmic - Frequency: 1Hz - Normal force detection → if it exceeds 10N as a result of specimen shrinkage, jump to further section where parameters were changed (see second section) Section 2 - Temperature gradient: further cooling to -50°C at 2K / min. - Deformation: constant 0.01% - Frequency: 1Hz - Normal force adjustment - 1N (this allows the gap to be adjusted and the thermal contraction of the material to be compensated)
[0135] The reported melt viscosities (mPa·s) are interpolated values of the complex viscosity at temperatures of 80°C or 120°C.
[0136] - Silicon content (wt%Si) The silicon content was measured by ICP (inductively coupled plasma) optical emission spectroscopy. Samples were digested by closed melt digestion (Wurzschmitt digestion) with sodium peroxide. ICP-OES measurements are based on ISO11885 ("Water quality - Determination of selected elements by inductively coupled plasma optical emission spectrometry (ICP-OES) (ISO11885:2007), German version EN ISO11885:2009"), which is used for the analysis of acidic aqueous solutions (e.g. acidified drinking water, wastewater, and other water samples, as well as aqua regia extracts of soils and sediments).
[0137] - Methanol value: For the measurement of the methanol value, defined mixtures of water and methanol are prepared. In separate experiments, these water-methanol mixtures are overlayered with an equal volume of dry particles and shaken under defined conditions (e.g. shaking gently by hand or in a tumble mixer for about 1 minute). Water-alcohol mixtures in which the particles have not yet sunk and water-alcohol mixtures with a higher alcohol content in which the particles have just sunk are measured. The latter methanol content in water gives the methanol value.
[0138] - The kinematic viscosity is determined according to DIN 53019 at 25°C.
[0139] In the following examples, all amounts and percentages are by weight, all pressures are 0.10 MPa (absolute) and all temperatures are 20° C., unless otherwise stated in any case. EXAMPLES
[0140] [Table 1]
[0141] Silica 1 is a partially hydrophobized, partially water-wettable fumed silica (E) according to EP 1 433 749 A1 used according to the invention.
[0142] Silica 2 is a non-inventive hydrophobic fumed silica according to US11078338BB.
[0143] [Table 2]
[0144] Example 1: Preparation of an aqueous silica dispersion (H) containing 20% by weight of silica 1 (invention) 200m 2 1300 g of partially water-wettable silica 1 with a carbon content of 0.9% and a methanol value of 5% by weight, obtained by reacting a hydrophilic starting silica with a BET specific surface area of 1000 g / g (available under the name HDK®N20 from Wacker-Chemie GmbH, Munich) with dimethyldichlorosilane according to EP1433749A1, is stirred in portions at 650 rpm into 5200 g of demineralized water in a dissolver. At the end of the addition of the silica, the mixture is further dispersed for another 60 minutes at 650 rpm. A highly viscous dispersion is obtained with a solids content of 20% and a pH of 4.2.
[0145] <General working instructions AA1 for transesterification of polyester (invention)> The thermoplastic polyester (C) and the end stoppers (I) are melted in a commercial vertical kneader (Grieser Maschinenbau-und Service GmbH, Chemiestraße 19-21, 68623 Lampertheim, Germany) at an internal temperature of 150° C. A condensation catalyst is then added and the mixture is kneaded at 150° C. for 16 hours. During the reaction, the melt viscosity of the mixture decreases, which results in a decrease in the power consumption of the kneader. The power consumption is stable after about 2 hours. At the end of the mixing time, the hot melt is poured onto a Teflon® film, cooled to room temperature and then crushed.
[0146] [Table 3]
[0147] [Example 7: Preparation of silica-coated poly-ε-caprolactone (PCL) particles (A) (present invention)] 120 g of the silica dispersion from Example 1 and 160 g of Placcel H1P (Daicel Corporation) were heated to 80° C. in a commercially available Labotop planetary mixer (PC Laborsystem GmbH, Meispracherstrasse 6, 4312 Magden, Switzerland) equipped with a paddle stirrer, dissolver disc and scraper. Once the polyester was completely melted, the mixture was dispersed at 6000 rpm for 10 min. A high-viscosity white polymer emulsion was produced.
[0148] The resulting homogeneous emulsion was diluted with 230 g of hot (80° C.) demineralized water at a dissolver speed of 3000 rpm and cooled to room temperature. For isolation, the particles of the invention (A) were filtered off and dried in a drying oven at 40° C. for 24 hours. A fine white powder is obtained. Examination by scanning electron microscope (SEM) shows that the particle surface is completely covered with silica and that the particles are non-porous. The analytical data are summarized in Table 4.
[0149] Example 8: Preparation of silica-coated poly(butylene succinate-co-adipate) (PBSA) particles (A) (present invention) 240 g of the silica dispersion from Example 1 and 320 g of transesterified poly(butylene succinate-co-adipate) (PBSA) from Example 2 were heated to 90° C. in a commercially available Labotop planetary mixer (PC Laborsystem GmbH, Meispracherstrasse 6, 4312 Magden, Switzerland) equipped with a paddle stirrer, dissolver disc and scraper. Once the polyester was completely melted, the mixture was dispersed at 6000 rpm for 10 min. A high-viscosity white polymer emulsion was produced.
[0150] The resulting homogeneous emulsion was diluted with 500 g of hot (90° C.) demineralized water at a dissolver speed of 3000 rpm and cooled to room temperature. For isolation, the particles A of the invention were filtered off and dried in a drying oven at 40° C. for 24 hours. A fine white powder was obtained. Examination by scanning electron microscope (SEM) showed that the particle surface was completely covered with silica and that the particles were non-porous. The analytical data are summarized in Table 4.
[0151] [Example 9: Preparation of silica-coated polyester particles (A) made of polyester having a melting temperature of 90 to 160°C] A Versoclave laboratory pressure reactor (Buechi AG, Gschwadelstrasse 12, 8610 Uster, Switzerland) was charged with 113 g of the silica dispersion from Example 1 and 191 g of the transesterified polyester from any of the invention examples 3-6. The unit was closed, pressurized with nitrogen to 10 bar and heated to an internal temperature of 150° C. The mixture was then mixed at 2500 rpm for 10 min. The stirring speed was reduced to 500 rpm, the mixture was cooled to room temperature and depressurized. The resulting homogeneous particle dispersion was diluted with 200 g of demineralized water at 500 rpm. For isolation, the inventive particles A were filtered off and dried in a drying oven at 40° C. for 24 h. A fine white powder is obtained. Examination by electron microscopy (SEM) showed that the particle surface was completely covered with silica and that the particles were non-porous. The analytical data are summarized in Table 4.
[0152] [Comparative Example V1: Modification of Example 3 from EP3489281A1 (non-invention)] According to Example 3 of EP3489281A1, 40 g of BioPBS™ FZ71 (Mitsubishi Chemical Performance Polymers), 60 g of 3-methyl-3-methoxybutanol (99%, Acros Organics™) and a dispersion of 3 g of hydrophobic silica 2 in 100 g of demineralized water were mixed in a Versoclave laboratory pressure reactor (Buechi AG, Gschwadelstrasse 12, 8610 Uster, Switzerland). The mixture was stirred for 90 min at 120° C. and 400 rpm and then cooled rapidly to room temperature while stirring. For isolation, the non-inventive particles were filtered off and dried in a drying oven at 40° C. for 24 h. A clumpy white powder is obtained. Examination by electron microscopy (SEM) shows that the particle surface is only partially covered with silica and that the particles have a porous structure. The analytical data are summarized in Table 4.
[0153] [Comparative Example V2: Modification of Example 5 from EP3489281A1 (non-invention)] Analogous to Example 5 of EP 3489281 A1, 60 g of BioPBS™ FZ71 (Mitsubishi Chemical Performance Polymers), 180 g of 3-methyl-3-methoxybutanol (99%, Acros Organics™) and a dispersion of 3 g of hydrophobic silica 2 in 360 g of demineralized water were mixed in a Versoclave laboratory pressure reactor (Buechi AG, 12, Uster-Gschwadelstrasse, 8610 Uster, Switzerland). The mixture was stirred for 90 min at 120° C. and 400 rpm and then cooled rapidly to room temperature while stirring. For isolation, the non-inventive particles were filtered off and dried in a drying oven at 40° C. for 24 h. A clumpy white powder is obtained. Examination by electron microscopy (SEM) shows that the particle surface is only partially covered with silica and that the particles have a porous structure. The analytical data are summarized in Table 4.
[0154] Comparative Example V3: Preparation of an aqueous silica dispersion containing 20% by weight of silica 2 (non-invention) The procedure was similar to that of Example 1, except that Silica 2 was used instead of Silica 1. Silica 2 was not completely dispersible in water and it was not possible to produce a suitable silica dispersion.
[0155] Comparative Example V4: Preparation of an aqueous silica dispersion (non-invention) containing 1.1% by weight of silica 2 The procedure was similar to that of Example 1, but 52 g of Silica 2 were used instead of Silica 1. A low viscosity dispersion with a solids content of 1% and a pH of 4.5 is obtained.
[0156] [Comparative Example V5 (Non-invention)] The procedure was similar to that of Inventive Example 3, except that the non-inventive silica dispersion of Comparative Example V4 was used instead of the inventive silica dispersion of Example 1. It was not possible to produce a homogeneous, finely divided particle dispersion.
[0157] [Comparative Example V6: Similar to Example 6 of EP3489281A1 (non-invention)] The procedure was similar to that of Example 6 of EP3489281A1, except that Silica 1 was used. 120 g BioPBS™ FZ71 (Mitsubishi Chemical Performance Polymers), 210 g 3-methyl-3-methoxybutanol (99%, Acros Organics™), and a dispersion of 9 g partially water-wettable Silica 1 in 270 g demineralized water were mixed in a Versoclave laboratory pressure reactor (Buechi AG, Gschwadelstrasse 12, 8610 Uster, Switzerland). The mixture was stirred at 120° C. and 400 rpm for 90 min, then cooled rapidly to room temperature while stirring. For isolation, the non-inventive particles were filtered off and dried in a drying oven at 40° C. for 24 h. A clumpy white powder is obtained. Examination by electron microscopy (SEM) shows that the particle surface is only partially covered with silica and that the particles have a porous structure. The analytical data are summarized in Table 4.
[0158] [Table 4]
[0159] [Example 14: Measurement of linseed oil adsorption amount] Linseed oil adsorption was measured according to the procedure described in EP3489281A1.
[0160] [Table 5]
[0161] [Example 17: Measurement of biodegradability] The biodegradability of the core-shell particles from invention examples 8, 9, 10, and 11 was measured by a CO2 evolution test according to OECD 301B. The core-shell particles from invention examples 8, 9, 10, and 11 met the criteria for "readily biodegradable."
[0162] [Example 18: Evaluation of dispersibility in water] Put 20 ml of demineralized water into the sample vessel and add 0.5 g of the particles to be evaluated. Close the vessel and shake the mixture vigorously 10 times. If the particles enter completely into the aqueous phase and a homogeneous single-phase dispersion is produced, the test is passed (+).
[0163] [Table 6]
Claims
1. Core-shell particles (A), A core (B) comprising a thermoplastic polyester (C) having a melting range of less than 160° C.; and A shell (D) comprising partially water-wettable particles (E) of a metal oxide having a methanol value of less than 30. is formed from The core-shell particles (A) have a metal content of at least 2.5% by weight.
2. A method for producing core-shell particles (A), comprising the steps of: The core-shell particles (A) are A core (B) comprising a thermoplastic polyester (C) having a melting range of less than 160° C.; and A shell (D) comprising partially water-wettable particles (E) of a metal oxide having a methanol value of less than 30. is formed from The metal content of the core-shell particles (A) is at least 2.5% by weight; In a first step, the thermoplastic polyester (C) is heated above its melting range, thereby becoming free flowing, and emulsified with particles (E) in water to form a particle-stabilized oil-in-water emulsion (G) having a discontinuous phase comprising molten polyester (C) and a water-containing continuous phase; In a second step, the emulsion (G) is cooled to below the melting range of the polyester (C), the molten particle-stabilized polyester droplets (C) are solidified, and the particles (E) are adhered to the surfaces of the polyester particles (C) to form core-shell particles (A).
3. The core-shell particle (A) according to claim 1 or the method according to claim 2, wherein the melting temperature of the thermoplastic polyester (C) is in the range of 45 to 160°C.
4. 4. The core-shell particle (A) according to claim 1 or 3 or the method according to claim 2 or 3, wherein the thermoplastic polyester (C) is selected from polycaprolactone (PCL), poly(butylene succinate) (PBS), poly(butylene succinate-adipate) (PBSA), poly(butylene adipate-terephthalate) (PBAT), polyhydroxyalkanoate (PHA), polyhydroxybutyrate (PHB), polyhydroxyvalerate (PHV), polyhydroxybutyrate-hydroxyvalerate copolymer (PHBV) or a mixture thereof.
5. 5. The core-shell particles (A) according to claim 1, 3 or 4 or the method according to claims 2 to 4, wherein the particles (E) are particles of aluminium(III) oxide, titanium(IV) oxide or silicon(IV) oxide.
6. The particles (E) are 30 to 500 m 2 The core-shell particles (A) according to claim 1 or any one of claims 3 to 5, or the method according to claims 2 to 5, having a BET specific surface area of 1 / g.
7. 7. The core-shell particles (A) according to claim 1 or 3 to 6 or the method according to claims 2 to 6, wherein the particles (E) have a Mohs hardness of more than 1.
8. The core-shell particles (A) according to claim 1 or 3 to 7 or the method according to claims 2 to 7, wherein said particles (E) have a methanol value of less than 30.
9. 9. Core-shell particles (A) according to claim 1 or 3 to 8 or the process according to claims 2 to 8, wherein the silicon content is at least 2% by weight, based on the core-shell particles (A).
10. The method according to claims 2 to 9, wherein the particle-stabilized oil-in-water emulsion (G) has a continuous aqueous phase containing at least 80% by weight of water.
11. The method according to claims 2 to 10, wherein the particle-stabilized oil-in-water emulsion (G) contains 1% to 20% by weight of partially water-wettable particles (E).
12. 12. The method according to claims 2 to 11, wherein said particle-stabilized oil-in-water emulsion (G) contains 50% to 80% by weight of a molten and thereby free-flowing thermoplastic polyester (C).
13. The method according to any one of claims 2 to 12, wherein in the first step, the polyester (C) heated above the melting range is emulsified with the exclusion of organic solvents.
Citation Information
Patent Citations
Method for preparing polymer microsphere from micro-nano bioactive glass as Pickering emulsion stable particle
CN107129585A
Crosslinked polyamino acid-containing particle having crosslinked surface
JP2001131283A
Solvent-free bio-based emulsion
JP2012126898A
Non-dehumidifying porous membrane
JP2012522882A
Composition having a hot melt resin matrix
JP2015531417A